2023
DOI: 10.1021/acscatal.3c02087
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Induced Formal Trifluoropropanation of Organic Halides

Abstract: CF3-containing molecules are frequently encountered in many best-selling pharmaceutical drugs. Consequently, a large number of methods have been developed for introducing a CF3 group into organic compounds. However, innovative protocols enabling direct access to alkyl-CF3 moieties are still sought after. In this context, we report a visible-light-induced formal trifluoropropanation of various alkyl and aryl halide derivatives using the 2-Bromo-3,3,3-trifluoro-1-propene (BTP) as a readily available building blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Apart from α-trifluoromethyl (hetero)­aryl alkenes, trifluoromethyl eneyne was also competent substrate, thus furnishing the difluoroalkene 2z with excellent regioselectivity, albeit in low yield. It was worth mentioning that the functionalization of α-trifluoromethyl alkenes with intact trifluoromethyl group in the product still remains a challenge . Herein, substrate containing a strongelectron-withdrawing aldehyde group chemo-selectively proceeded the hydroformylation pathway to afford 4 as single product in 65% yield, which was in contrast to the defluoro-formylation pathway in most cases.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from α-trifluoromethyl (hetero)­aryl alkenes, trifluoromethyl eneyne was also competent substrate, thus furnishing the difluoroalkene 2z with excellent regioselectivity, albeit in low yield. It was worth mentioning that the functionalization of α-trifluoromethyl alkenes with intact trifluoromethyl group in the product still remains a challenge . Herein, substrate containing a strongelectron-withdrawing aldehyde group chemo-selectively proceeded the hydroformylation pathway to afford 4 as single product in 65% yield, which was in contrast to the defluoro-formylation pathway in most cases.…”
Section: Resultsmentioning
confidence: 99%
“…They were purchased from Sigma-Aldrich, Alfa Aesar, Fluorochem, and TCI Europe and used without further purification. Starting materials 2c , 2e , 2f , 2g , 2h , 2i – 2j , 2l-I , 2m - 2o , 2t - 2v , and 2w were synthesized according to described procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Concomitantly to this work, we have demonstrated that light-induced radical β-bromo or iodo fragmentation can be key to achieving hydrohalogenation of unsaturated compounds under visiblelight irradiation. [15] In this context and given our recent interest for fluorination reactions, [16] we envisaged to explore the possibility of synthesizing gem-difluoroal-kenes by the use of readily available oxime ester derivatives and 1-bromo-1,1-difluoroprop-2-ene (BDFP). Indeed, such oximes have recently been shown to be efficient radical precursors for achieving a large panel of organic reactions.…”
Section: Introductionmentioning
confidence: 99%